Jelena Tomić-Bokur (1889–1961) – the First State-Appointed Woman Engineer Architect in Yugoslavia - Ladinski, Vladimir B. (History of Engineering Sciences and Institutions of Higher Education, 2024)
In 2023, the author’s study «Early Engineers and Architects Born on the Territory of Present North Macedonia» was published in the RTU RCEH Scientific Journal «History of Engineering Sciences and Institutions of Higher Education» about the first engineers and architects who were born in the territory of present-day North Macedonia. This paper focuses on the life and work of the first state-appointed woman engineer architect in Yugoslavia in 1919, Jelena Tomić-Bokur (nee Tomić; 1889–1961), a graduate of the Technical Faculty of the University of Belgrade in 1913. The paper covers in brief her 24-year-long professional career between 1913 and 1937 in the Kingdom of Serbia and the Kingdom of Serbs, Croats, and Slovenes – Yugoslavia, with emphasis on her formation years in Skopje (1915–1923). This study contributes to the history of engineering and architecture in North Macedonia and wider whilst exploring the context in which the first women professionals emerged in Serbia and former Yugoslavia.